High-strength and large-pore-volume catalytic cracking aid and preparation method thereof
Through the combination of H-type ZSM-5 molecular sieve with iron atom doping and mesoporous structure, a high-strength, large-porous catalytic cracking additive was prepared, and the ZSM-5 molecular sieve micro-sieve was solved The diffusion restriction problem caused by pore structure improves the efficiency and selectivity of catalytic reactions.
Patent Information
- Application Number
- CN202411239577.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2024-12-13
AI Technical Summary
The micropore structure of ZSM-5 molecular sieve is relatively narrow, resulting in limited diffusion of oil and gas macromolecules, aggregation of reactants or products, and side reactions occur, causing difficulty in mass transfer of catalytic reactions and reducing the selectivity of target products.
High-strength, large-porous catalytic cracking additives are prepared by using H-type ZSM-5 molecular sieve doped iron atoms and mesoporous structures, along with kaolin, phthalidite, and aluminum sol. Through N1,N5-dadecyl- N1,N1,N5,N5-tetramethylpentan-1,5-diammonium bromide and choline chloride were used as mixed template agents to induce the formation of reticular spherical HZSM-5 molecular sieve, increasing pore volume and acid amount.
The catalytic selectivity and activity are improved, the conversion rate of raw oil and propylene yield are enhanced, the occurrence of side reactions is reduced, and the efficiency of catalytic reactions is improved.
Smart Images

Figure CN119114145A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of catalytic cracking aids, and more specifically, to a high-strength, large-pore-volume catalytic cracking aid and a preparation method thereof. Background Art
[0002] As an important petrochemical raw material, propylene can produce a series of important propylene derivatives after polymerization, hydrocarbonization (alkylation), hydration, oxidation, chlorination, ammoxidation, carbonylation and oligomerization. Increasing propylene production by adding propylene production-increasing additives to catalytic cracking catalysts is a flexible, efficient and side-effect-free preferred solution. It does not require equipment modification, does not significantly change product structure and quality conditions, is simple to operate, has low cost and high efficiency. ZSM-5 molecular sieves are widely used in catalytic cracking catalysts and additives to increase the production of light olefins due to their unique "Zig-Zag" pores, strong acidity, good hydrothermal stability and efficient shape-selective catalysis. However, in actual use, due to the relatively narrow and single micropore structure of the ZSM-5 molecular sieve, there are obvious diffusion restrictions on large oil and gas molecules in the pores. The accessibility of large oil and gas molecules to the active sites in the micropores is very poor, causing the reactants or products to accumulate on the acid center and excessive cracking, side reactions to occur, or coking of the pores, which seriously affects the diffusion of larger reactant and product molecules, causing mass transfer difficulties in the catalytic reaction and reducing the selectivity of the target product. Summary of the invention
[0003] In order to further improve the catalytic selectivity and catalytic activity of ZSM-5 molecular sieve, the present application provides a high-strength, large-pore volume catalytic cracking aid and a preparation method thereof.
[0004] In the first aspect, the present application provides a high-strength, large-pore-volume catalytic cracking aid, which adopts the following technical solution: A high-strength, large-pore-volume catalytic cracking aid comprises the following components: 32-43 parts of kaolin, 18-22 parts of pseudo-boehmite, 8-12 parts of aluminum sol, and 30-38 parts of HZSM-5 molecular sieve; the HZSM-5 molecular sieve is an H-type ZSM-5 molecular sieve doped with iron atoms and having a mesoporous structure.
[0005] By adopting the above technical scheme, the H-type ZSM-5 molecular sieve doped with iron atoms and having a mesoporous structure is prepared together with kaolin, pseudo-boehmite and aluminum sol to obtain a catalytic cracking aid with high strength, large pore volume and high total acid. It can be used in propylene production to better improve the conversion rate of raw oil and the yield of propylene.
[0006] Preferably, the HZSM-5 molecular sieve is prepared by the following steps: S1, sodium hydroxide, aluminum source, mixed template, deionized water, stirred and mixed, then silicon source was slowly added dropwise, then ferric nitrate was added, and finally, a pretreatment solution of ZSM-5 molecular sieve seed was added, stirring was continued for 2-3 hours at room temperature, and then the mixture was transferred to a hydrothermal reactor for crystallization. After the crystallization was completed, the product was filtered, washed with water until the pH value of the filtrate was 7, dried at 115-125°C for 10-12 hours, and calcined at 540-560°C for 3.5-4.5 hours. , obtaining a ZSM-5 molecular sieve; S2, ion-exchanging the ZSM-5 molecular sieve in an aqueous ammonium chloride solution at 80-85°C for 40-60min, filtering and washing until the pH value of the filtrate is 7, repeating the ion-exchange once, drying at 115-125°C for 8-10h, and calcining at 540-560°C for 3.5-4.5h to obtain a HZSM-5 molecular sieve; the mixed template agent includes N1,N5-didecyl-N1,N1,N5,N5-tetramethylpentane-1,5-diammonium bromide and choline chloride.
[0007] By adopting the above technical scheme, N1,N5-didecyl-N1,N1,N5,N5-tetramethylpentane-1,5-diammonium bromide and choline chloride are used as mixed templates. On the one hand, N1,N5-didecyl-N1,N1,N5,N5-tetramethylpentane-1,5-diammonium bromide is a symmetrical medium-chain diquaternary ammonium salt structure, which can induce the HZSM-5 molecular sieve to generate nanometer-thick strip grains and form a large number of mesopores with smaller pore sizes. On the other hand, the occupancy effect of choline chloride can induce iron metal to enter the framework of the ZSM-5 molecular sieve. The finally prepared HZSM-5 molecular sieve is in the shape of a reticulated sphere, has a large pore volume, a mesopore diameter of 5-10 nanometers, and a high acid content.
[0008] Preferably, the silicon source, aluminum source, sodium hydroxide, N1,N5-didecyl-N1,N1,N5,N5-tetramethylpentane-1,5-diammonium bromide, choline chloride, ferric nitrate, and water are mixed in a molar ratio of n(SiO 2 )∶n(Al 2 O 3 )∶n(NaOH)∶n(C 33 H 72 Br 2 N 2 )∶n(C 5 H 14 ClNO)∶n(Fe 2 O 3 )∶n(H 2The dosage ratio of the invention is 0.0028-0.0032: (0.22-0.26): (0.02-0.04): (0.04-0.06): (0.003-0.005): (1200-1500).
[0009] By adopting the above technical solution, the mesopores of the HZSM-5 molecular sieve prepared by using the above dosage ratio are relatively small, and more iron metal enters the molecular sieve framework.
[0010] Preferably, the aluminum source is one or more of aluminum isopropoxide, aluminum sulfate, aluminum hydroxide, and sodium aluminate.
[0011] Preferably, the silicon source is one or more of silica sol, ethyl orthosilicate, water glass, white carbon black, and silica gel.
[0012] By adopting the above technical solution, the HZSM-5 molecular sieve prepared by using the above aluminum source and silicon source has better performance.
[0013] Preferably, the ZSM-5 molecular sieve: ammonium chloride: H 2 The mass ratio of O is 10-12:4.5-5.5:45-60.
[0014] By adopting the above technical solution, the sodium-type ZSM-5 molecular sieve can be fully converted into the H-type ZSM-5 molecular sieve (ie, HZSM-5).
[0015] Preferably, the amount of the ZSM-5 molecular sieve seed added is SiO 2 4%-6% of mass fraction.
[0016] By adopting the above technical solution, adding ZSM-5 molecular sieve seed crystals can promote the formation of ZSM-5 crystal nuclei and accelerate the crystallization rate of ZSM-5 molecular sieve.
[0017] Preferably, the high-strength, large-pore-volume catalytic cracking aid according to claim 7 is characterized in that the crystallization temperature in S1 is 160-180° C. and the crystallization time is 20-26 h.
[0018] By adopting the above technical solution, the degree of crystallization is high.
[0019] Preferably, the pretreatment of the ZSM-5 molecular sieve seed crystals is as follows: 4-6 g of ZSM-5 molecular sieve seed crystals are added to 18-20 mL of 10-12 wt % ammonium hexafluorosilicate solution, and ultrasonicated at 65-75° C. for 20-30 min to obtain a pretreated solution of the ZSM-5 molecular sieve seed crystals.
[0020] By adopting the above technical solution, the ZSM-5 molecular sieve seed crystals can be pretreated to shorten the time required for crystallization.
[0021] In summary, this application has the following beneficial effects: 1. The present application uses N1,N5-didecyl-N1,N1,N5,N5-tetramethylpentane-1,5-diammonium bromide and choline chloride as mixed templates, adds a pretreatment solution of ZSM-5 molecular sieve seeds, introduces an iron source by adding ferric nitrate, and crystallizes for a certain period of time by a hydrothermal method to obtain a ZSM-5 molecular sieve, and then prepares an HZSM-5 molecular sieve by ion exchange with ammonium chloride, and finally prepares a high-strength, large-pore volume catalytic cracking aid together with kaolin, pseudo-boehmite, and aluminum sol.
[0022] 2. In the present application, N1,N5-didecyl-N1,N1,N5,N5-tetramethylpentane-1,5-diammonium bromide and choline chloride are preferably used as mixed templates, which can induce the generated HZSM-5 molecular sieve to be in the shape of a reticulated sphere, with a large pore volume and a mesopore diameter of 5-10 nanometers. At the same time, it is found that choline chloride can promote the entry of iron metal into the framework of the ZSM-5 molecular sieve and increase the acid content.
[0023] 3. The catalytic cracking aid prepared by the preparation method of the present application can be used in propylene production to better improve the conversion rate of raw oil and the yield of propylene. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 : XRD pattern of the HZSM-5 molecular sieve prepared in Example 2 of the present application.
[0025] Figure 2 : SEM images of the HZSM-5 molecular sieve prepared in Example 2 of the present application, wherein: (a) Comparative Example 1, (b) Comparative Example 2, (c) Comparative Example 3, and (d) Example 2.
[0026] Figure 3 : UV-Vis graph of the HZSM-5 molecular sieve prepared in Example 2 of the present application.
[0027] Figure 4 : N of the HZSM-5 molecular sieve prepared in Example 2 of the present application 2 Adsorption-desorption isotherm plot. DETAILED DESCRIPTION
[0028] The present application is further described in detail below with reference to the embodiments.
[0029] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.
[0030] ZSM-5 molecular sieve seed crystals were purchased from Zhuoyue Environmental Protection New Materials (Shanghai) Co., Ltd., model NA-H05-B04M. Example Example 1
[0031] A high-strength, large-pore-volume catalytic cracking aid comprises the following components: 32 parts of kaolin, 18 parts of pseudo-boehmite, 8 parts of aluminum sol, and 30 parts of HZSM-5 molecular sieve.
[0032] The HZSM-5 molecular sieve is prepared by the following steps: S1, after stirring and mixing sodium hydroxide, aluminum source, mixed template agent, and deionized water, slowly dropwise add silicon source, then add ferric nitrate, and finally add pretreatment solution of ZSM-5 molecular sieve seed crystal, continue stirring at room temperature for 2 hours, then transfer to a hydrothermal reactor, crystallize at 160°C for 20 hours, after the crystallization is completed, filter the product, wash with water until the pH value of the filtrate is 7, dry at 115°C for 10 hours, and calcine at 540°C for 3.5 hours to obtain ZSM-5 molecular sieve; The aluminum source is aluminum isopropoxide.
[0033] The silicon source is water glass.
[0034] The silicon source, aluminum source, sodium hydroxide, N1,N5-didecyl-N1,N1,N5,N5-tetramethylpentane-1,5-diammonium bromide, choline chloride, ferric nitrate, and water are mixed according to a molar ratio of n (SiO 2 )∶n(Al 2 O 3 )∶n(NaOH)∶n(C 33 H 72 Br 2 N 2 )∶n(C 5 H 14 ClNO)∶n(Fe 2 O 3 )∶n(H 2 O) = 1∶0.0028∶0.22∶0.02∶0.04∶0.003∶1200. 33 H 72 Br 2 N 2 Refers to N1,N5-didecyl-N1,N1,N5,N5-tetramethylpentane-1,5-diammonium bromide, C 5 H 14 ClNO refers to choline chloride.
[0035] The amount of ZSM-5 molecular sieve seed added is SiO 2 4% by mass.
[0036] The ZSM-5 molecular sieve seed crystals were added after the following pretreatment: 4 g of ZSM-5 molecular sieve seed crystals were added to 18 mL of 10 wt % ammonium hexafluorosilicate solution, and ultrasonicated at 65° C. for 20 min to obtain a pretreated solution of the ZSM-5 molecular sieve seed crystals.
[0037] S2, ion exchange the ZSM-5 molecular sieve in an aqueous solution of ammonium chloride at 80°C for 40 minutes, filter and wash until the pH value of the filtrate is 7, repeat the ion exchange once, dry at 115°C for 8 hours, and calcine at 540°C for 3.5 hours to obtain the HZSM-5 molecular sieve.
[0038] The ZSM-5 molecular sieve: ammonium chloride: H 2 The mass ratio of O is 10:4.5:45. Example 2
[0039] A high-strength, large-pore-volume catalytic cracking aid comprises the following components: 38 parts of kaolin, 20 parts of pseudo-boehmite, 10 parts of aluminum sol, and 35 parts of HZSM-5 molecular sieve.
[0040] The HZSM-5 molecular sieve is prepared by the following steps: S1, sodium hydroxide, aluminum source, mixed template, deionized water, stirred and mixed, then slowly added silicon source, then added ferric nitrate, finally, added ZSM-5 molecular sieve seed pretreatment solution, continued stirring at room temperature for 2.5 hours, then transferred to a hydrothermal reactor, crystallized at 170°C for 24 hours, after the crystallization, filtered the product, washed with water until the pH value of the filtrate was 7, dried at 120°C for 11 hours, and calcined at 550°C for 4 hours to obtain ZSM-5 molecular sieve; The aluminum source is sodium aluminate.
[0041] The silicon source is silica sol.
[0042] The silicon source, aluminum source, sodium hydroxide, N1,N5-didecyl-N1,N1,N5,N5-tetramethylpentane-1,5-diammonium bromide, choline chloride, ferric nitrate, and water are mixed according to a molar ratio of n (SiO 2 )∶n(Al 2 O 3 )∶n(NaOH)∶n(C 33 H 72 Br 2 N 2 )∶n(C 5 H 14 ClNO)∶n(Fe 2 O 3 )∶n(H 2 The dosage ratio of O) is 1:0.0030:0.24:0.03:0.05:0.004:1350.
[0043] The added amount of the ZSM-5 molecular sieve seed crystal is 5% of the mass fraction of SiO2.
[0044] The ZSM-5 molecular sieve seed crystals were added after the following pretreatment: 5 g of ZSM-5 molecular sieve seed crystals were added to 19 mL of 11 wt % ammonium hexafluorosilicate solution, and ultrasonicated at 70° C. for 25 min to obtain a pretreated solution of the ZSM-5 molecular sieve seed crystals.
[0045] S2, ion exchange the ZSM-5 molecular sieve in an aqueous solution of ammonium chloride at 82°C for 50 min, filter and wash until the pH value of the filtrate is 7, repeat the ion exchange once, dry at 120°C for 9 h, and calcine at 550°C for 4 h to obtain the HZSM-5 molecular sieve.
[0046] The ZSM-5 molecular sieve: ammonium chloride: H 2 The mass ratio of O is 11:5:52. Example 3
[0047] A high-strength, large-pore-volume catalytic cracking aid comprises the following components: 43 parts of kaolin, 22 parts of pseudo-boehmite, 12 parts of aluminum sol, and 38 parts of HZSM-5 molecular sieve.
[0048] The HZSM-5 molecular sieve is prepared by the following steps: S1, sodium hydroxide, aluminum source, mixed template, deionized water, stirred and mixed, then slowly added silicon source, then added ferric nitrate, finally, added ZSM-5 molecular sieve seed pretreatment solution, continued stirring at room temperature for 3 hours, then transferred to a hydrothermal reactor, crystallized at 180°C for 26 hours, after the crystallization, filtered the product, washed with water until the pH value of the filtrate was 7, dried at 125°C for 12 hours, and calcined at 560°C for 4.5 hours to obtain ZSM-5 molecular sieve; The aluminum source is aluminum sulfate.
[0049] The silicon source is tetraethyl orthosilicate.
[0050] The silicon source, aluminum source, sodium hydroxide, N1,N5-didecyl-N1,N1,N5,N5-tetramethylpentane-1,5-diammonium bromide, choline chloride, ferric nitrate, and water are mixed according to a molar ratio of n (SiO 2 )∶n(Al 2 O 3 )∶n(NaOH)∶n(C 33 H 72 Br 2 N 2 )∶n(C 5 H 14 ClNO)∶n(Fe 2 O3 )∶n(H 2 The dosage ratio of the product is 1:0.0032:0.26:0.04:(0.04-0.06):0.005:1500.
[0051] The amount of ZSM-5 molecular sieve seed added is SiO 2 6% by mass.
[0052] The ZSM-5 molecular sieve seed crystals were added after the following pretreatment: 6 g of ZSM-5 molecular sieve seed crystals were added to 20 mL of 10-12 wt % ammonium hexafluorosilicate solution, and ultrasonicated at 75° C. for 30 min to obtain a pretreated solution of the ZSM-5 molecular sieve seed crystals.
[0053] S2, ion exchange the ZSM-5 molecular sieve in an aqueous solution of ammonium chloride at 85°C for 60 minutes, filter and wash until the pH value of the filtrate is 7, repeat the ion exchange once, dry at 125°C for 10 hours, and calcine at 560°C for 4.5 hours to obtain the HZSM-5 molecular sieve.
[0054] The ZSM-5 molecular sieve: ammonium chloride: H 2 The mass ratio of O is 12:5.5:60.
[0055] Comparative Example
[0056] Comparative Example 1 The same as Example 2, except that N1,N5-didecyl-N1,N1,N5,N5-tetramethylpentane-1,5-diammonium bromide is replaced with 2 times the molar amount of tetrabutylammonium bromide.
[0057] Comparative Example 2 The same as Example 2, except that N1,N5-didecyl-N1,N1,N5,N5-tetramethylpentane-1,5-diammonium bromide is replaced with a 2-fold molar amount of tetrapropylammonium hydroxide.
[0058] Comparative Example 3 The same as Example 2, except that N1,N5-didecyl-N1,N1,N5,N5-tetramethylpentane-1,5-diammonium bromide is replaced with 2 times the molar amount of octadecylammonium bromide.
[0059] Comparative Example 4 The same as Example 2, except that choline chloride is removed.
[0060] Performance test experiment
[0061] The HZSM-5 molecular sieve prepared in Example 2 and the commercially available conventional H-ZSM-5 (i.e., H-type ZSM-5) molecular sieve were subjected to XRD tests using an X-ray polycrystalline diffractometer. Figure 1 shown.
[0062] As shown in Figure 1, both molecular sieves θ Characteristic peaks appear at 7.9°, 8.8°, 14.8°, 23.1°, 23.9°, and 24.4°, and there are no impurity peaks; the characteristic peaks are respectively attributed to the characteristic diffraction of the (011), (020), (015), (511), and (313) crystal planes of the ZSM-5 molecular sieve, indicating that the molecular sieve prepared in the present application is a HZSM-5 molecular sieve with a typical MFI framework structure. In addition, the absence of impurity peaks indicates that the doping of iron atoms and ion exchange will not affect the crystal phase of the molecular sieve.
[0063] The surface morphology of the molecular sieves prepared in Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3 was measured using a scanning electron microscope. Figure 2 shown.
[0064] from Figure 2 It can be seen that the HZSM-5 molecular sieve prepared in Comparative Example 1 is rectangular, with uniform particle size distribution and a grain size of about 1.1 microns; the HZSM-5 molecular sieve prepared in Comparative Example 2 is spherical, with a smooth surface, no obvious agglomeration between the grains, and a particle size of about 130 nanometers; the particle size of the HZSM-5 molecular sieve prepared in Comparative Example 3 has increased to between 150 and 220 nanometers, and the roundness of the particles has slightly decreased; the HZSM-5 molecular sieve prepared in Example 2 is larger, about 2.5 microns, and has a reticular spherical structure, and the reticular pattern is formed by the aggregation and staggered growth of strip-like grains 25 to 45 nanometers thick.
[0065] The coordination state of iron in the HZSM-5 molecular sieves prepared in Example 2 and Comparative Example 4 was analyzed by an ultraviolet spectrophotometer (UV-vis). Figure 3 shown.
[0066] from Figure 3 It can be seen that compared with conventional H-ZSM-5 molecular sieves, the iron-doped HZSM-5 molecular sieve has absorption peaks at around 230 nanometers and 280 nanometers. Among them, the absorption peak at 230 nanometers corresponds to the four-coordinated structure of Fe 3+ ; The absorption peak at 280 nm corresponds to the six-coordinated structure of Fe 3+ , which means that not all of the Fe metal enters the molecular sieve framework, a part of it enters the molecular sieve framework in the form of four coordination, and the other part exists in the molecular sieve framework in the form of six coordination. Compared with Comparative Example 2, the two absorption peaks of Example 2 are significantly smaller, indicating that under the action of choline chloride, Fe metal is more likely to enter the molecular sieve framework.
[0067] The pore structures of Example 2 and Comparative Examples 1 to 3 were analyzed using a fully automatic physical adsorption instrument. The results are as follows: Figure 4 And as shown in Table 1.
[0068] from Figure 4 It can be seen that the HZSM-5 molecular sieve prepared in Comparative Example 1 is a type I isotherm. When the relative pressure increases, the adsorption amount of nitrogen does not increase significantly with the increase of relative pressure, and no obvious hysteresis loop appears, which is a characteristic of microporous materials, indicating that it mainly contains micropores; the HZSM-5 molecular sieve prepared in Comparative Example 2 is a type IV isotherm. When the relative pressure is 0.9, the adsorption amount of nitrogen rises rapidly, and an H1-type hysteresis loop appears, indicating that it has more large mesopores; the adsorption isotherm type of Comparative Example 3 is type IV, with an H1-type hysteresis loop. Compared with Comparative Example 2, the nitrogen adsorption amount is larger and the hysteresis loop is more obvious, indicating that it has more mesopores; the adsorption isotherm of Example 2 is type IV, with a wider H4-type hysteresis loop within the relative pressure value of 0.4-1, indicating that it contains a large number of mesopores and macropore structures.
[0069] In addition, the desorption branch calculation shows that Example 1 is almost entirely micropores, while Examples 2 and 3 are mainly mesopores of about 35 nanometers, and Example 3 has more mesopores, while Example 2 has the highest mesopore content, and the mesopore diameters are concentrated in the range of 5-10 nanometers.
[0070] Table 1. Pore structure of HZSM-5 molecular sieve
[0071] It can be seen from Table 1 that the HZSM-5 molecular sieve prepared in Example 2 of the present application has a higher specific surface area and pore volume.
[0072] The acid content of H-ZSM-5 and the HZSM-5 molecular sieves prepared in Example 2 and Comparative Examples 1 to 4 was determined by using a fully automatic multi-purpose adsorption instrument using the NH3 programmed temperature desorption method. The results are shown in Table 2.
[0073] Table 2. Acid content of HZSM-5 molecular sieve
[0074] It can be seen from Table 2 that the HZSM-5 molecular sieve prepared in Example 2 of the present application has a higher acid content, and the total acid content is from large to small in the order of Example 2> Comparative Example 3> Comparative Example 2> Comparative Example 1> Comparative Example 4> H-ZSM-5.
[0075] The HZSM-5 molecular sieve prepared in Examples 1-3 and Comparative Examples 1-4 was added with kaolin, pseudo-boehmite, and aluminum sol, mixed and slurried, spray dried, and calcined at 500°C for 3.5h to obtain a catalytic cracking aid. Then, according to m (USY main agent) : m (catalytic cracking aid) of 9:1, the main agent and the catalytic cracking aid were aged at 850°C and 100% steam for 15h to obtain a catalyst, and its average lateral pressure strength was tested. The product selectivity of the catalyst was evaluated using a fixed fluidized bed ACE device. The catalyst loading was 10g, the catalyst / raw oil (using Wu Mixed Three Pipes for oil transportation) was 5.5, the raw oil flow rate was 1.0 g / min, and the reaction temperature was 550°C. The results are shown in Table 3: Table 3. Product selection of catalysts Active additives Average lateral compressive strength (N / cm) Raw oil conversion rate (%) Propylene yield (%) Example 1 100 85.5 8.96 Example 2 104 85.7 8.99 Example 3 103 86.1 8.97 Comparative Example 1 108 80.1 8.28 Comparative Example 2 93 81.5 8.41 Comparative Example 3 85 82.3 8.58 Comparative Example 4 81 83.4 8.71 H-ZSM-5 95 78.2 8.13 As can be seen from Table 3, the HZSM-5 molecular sieve prepared in the present application has higher mechanical strength and can better improve the crude oil conversion rate and propylene yield. The HZSM-5 molecular sieve prepared in Examples 1-3 of the present application is used as a catalytic activity additive. The crude oil conversion rate on the catalyst is as high as 86.1%, and the propylene yield is 8.99%, which is 7.9% and 0.83% higher than that of H-ZSM-5; the lateral pressure strength reaches 104N / cm.
[0076] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, a person skilled in the art may make non-creative modifications to the present embodiment as needed, and such modifications shall be protected by the patent law as long as they are within the scope of protection claimed in the present application.
Claims
1. A high-strength, large-pore-volume catalytic cracking aid, characterized in that: The invention comprises the following components: 32-43 parts of kaolin, 18-22 parts of pseudo-boehmite, 8-12 parts of aluminum sol and 30-38 parts of HZSM-5 molecular sieve; the HZSM-5 molecular sieve is an H-type ZSM-5 molecular sieve doped with iron atoms and having a mesoporous structure.
2. A high-strength, large-pore-volume catalytic cracking aid according to claim 1, characterized in that: The HZSM-5 molecular sieve is prepared by the following steps: S1, sodium hydroxide, aluminum source, mixed template agent, and deionized water are stirred and mixed, and then a silicon source is slowly added dropwise, and then ferric nitrate is added, and finally, a pretreatment solution of ZSM-5 molecular sieve seed crystals is added, and stirring is continued at room temperature for 2-3 hours, and then the mixture is transferred to a hydrothermal reactor for crystallization. After the crystallization is completed, the product is filtered, washed with water until the pH value of the filtrate is 7, dried at 115-125° C. for 10-12 hours, and calcined at 540-560° C. for 3.5-4.5 hours to obtain to ZSM-5 molecular sieve; S2, ion exchange the ZSM-5 molecular sieve in an aqueous solution of ammonium chloride at 80-85°C for 40-60min, filter and wash until the pH value of the filtrate is 7, repeat the ion exchange once, dry at 115-125°C for 8-10h, and calcine at 540-560°C for 3.5-4.5h to obtain HZSM-5 molecular sieve; the mixed template agent includes N1,N5-didecyl-N1,N1,N5,N5-tetramethylpentane-1,5-diammonium bromide and choline chloride.
3. A high-strength, large-pore-volume catalytic cracking aid according to claim 2, characterized in that: The silicon source, aluminum source, sodium hydroxide, N1,N5-didecyl-N1,N1,N5,N5-tetramethylpentane-1,5-diammonium bromide, choline chloride, ferric nitrate, and water are mixed according to a molar ratio of n(SiO2):n(Al2O3):n(NaOH):n(C 33 H 72 Br2N2)∶n(C5H 14 The composition is composed of a dosage ratio of ClNO)∶n(Fe2O3)∶n(H2O)=1∶(0.0028-0.0032)∶(0.22-0.26)∶(0.02-0.04)∶(0.04-0.06)∶(0.003-0.005)∶(1200-1500).
4. A high-strength, large-pore-volume catalytic cracking aid according to claim 3, characterized in that: The aluminum source is one or more of aluminum isopropoxide, aluminum sulfate, aluminum hydroxide, and sodium metaaluminate.
5. A high-strength, large-pore-volume catalytic cracking aid according to claim 4, characterized in that: The silicon source is one or more of silica sol, ethyl orthosilicate, water glass, white carbon black and silica gel.
6. A high-strength, large-pore-volume catalytic cracking aid according to claim 5, characterized in that: The mass ratio of the ZSM-5 molecular sieve: ammonium chloride: H2O is 10-12: 4.5-5.5: 45-60.
7. A high-strength, large-pore-volume catalytic cracking aid according to claim 6, characterized in that: The added amount of the ZSM-5 molecular sieve seed crystal is 4%-6% of the mass fraction of SiO2.
8. A high-strength, large-pore-volume catalytic cracking aid according to claim 7, characterized in that: In S1, the crystallization temperature is 160-180°C and the crystallization time is 20-26h.
9. A high-strength, large-pore-volume catalytic cracking aid according to claim 8, characterized in that: The pretreatment of the ZSM-5 molecular sieve seed crystals is as follows: 4-6 g of ZSM-5 molecular sieve seed crystals are added to 18-20 mL of a 10-12 wt % ammonium hexafluorosilicate solution, and ultrasonicated at 65-75° C. for 20-30 min to obtain a pretreatment solution of the ZSM-5 molecular sieve seed crystals.
